Changing Treatment and Metastatic Disease Patterns in Patients with EGFR Mutated NSCLC: An Academic Thoracic Medical Investigator’s Consortium Registry Analysis - Margaret Stalker, MD; Connor B. Grady, MPH; Alex Watts, MS; Wei-Ting Hwang, PhD; Krishna Chandrasekhara, MS; Fangdi Sun, MD; Geoffrey Liu, MD; Devalben Patel, MD; Jorge Nieva, MD; Amanda Herrmann, MD; Kristen Marrone, MD; Vincent K. Lam, MD; et al. (JTO Clinical and Research Reports)
Introduction: Osimertinib is now a standard first-line (1L) therapy for EGFR-mutated (EGFRm) advanced NSCLC. We aimed to characterize patterns of therapy and longitudinal risk of brain and liver metastasis in a cohort of EGFRm NSCLC. Methods: Patients with metastatic EGFRm NSCLC who received 1L systemic therapy at sites within the Academic Thoracic Medical Investigator’s Consortium were included; demographic and clinical data including treatment patterns were described. Analyses of overall survival, time to next treatment, and incident brain and liver metastasis were performed using the Kaplan-Meier method, Cox regression, and cumulative incidence functions on patients who started 1L therapy in 2015 or later. Results: The full cohort included 1132 patients and the mean age of the participants was 63.4 years; among the participants, 53% were White individuals, 68% were female individuals, and 67% were nonsmokers. Among the participants, 830 patients received 1L systemic therapy in 2015 or later. The predominant first EGFR–tyrosine kinase inhibitor was erlotinib (65%) before 2018 and osimertinib (81%) after 2018. The median time to the next treatment after the start of 1L therapy was 13.9 months overall and the longest in patients receiving 1L osimertinib (28 months). In the post-2015 cohort, the baseline prevalence of brain metastasis (BM) was 54% and among patients without baseline brain metastasis, the probability of incident BM at 12, 24, and 48 months was 8%, 22%, and 44%, respectively. Development of an on-treatment brain metastasis among patients without baseline brain metastasis was associated with a 3.2 times higher risk of death. Conclusion: Even in a contemporary era with prevalent osimertinib use, the baseline and longitudinal risk of BM development was high. The ongoing risk of developing BM, together with the associated survival detriment, argues for routine surveillance of the brain through magnetic resonance imaging for patients with EGFRm NSCLC, which is not currently included in the guidelines.